Performance validation of vehicle platooning through intelligible analytics. Issue 2 (8th January 2019) - Mongelli, Maurizio; Ferrari, Enrico; Muselli, Marco; Fermi, Alessandro
Abstract : The study deals with intelligible analytics for performance modelling of vehicle platooning. Knowledge extraction with rules is targeted to understand safety regions (collision avoidance) of system parameters. Results are shown by feeding data through simulation to the train of different rule extraction mechanisms. Safety regions are evidenced on test data with statistical error very close to zero.